Gut microbiota mediates the protective role of Lactobacillus plantarum in ameliorating deoxynivalenol-induced apoptosis and intestinal inflammation of broiler chickens - Yang, Xin; Liang, Saisai; Guo, Fangshen; Ren, Zhouzheng; Yang, Xiaojun; Long, Fangyu (Poultry science, 2020)
The protection of Lactobacillus plantarum JM113 against deoxynivalenol (DON)-induced apoptosis and intestinal inflammation on the jejunum of broiler chickens and the potential roles of gut microbiota were determined. A total of 144 one-day-old male broilers (Arbor Acres) were randomly divided into 3 treatment groups consisting of 6 replicates with 8 birds per replicate, including the CON (basal diet), the DON (basal diet + 10 mg/kg DON), and the DL (basal diet + 10 mg/kg DON + 1 × 109 CFU/kg L. plantarum JM113). The DON-diet decreased (P < 0.05) the mRNA expression of mucosal defense proteins and mechanistic target of rapamycin pathway genes. Meanwhile, DON challenge significantly increased Bcl-2-associated X gene/B-cell lymphoma 2 gene (Bcl-2) in the jejunum (P < 0.05) and demonstrated proapoptosis status. In contrast, the DL group showed normal immunity-related gene expression of jejunal mucosa and manifested a superior antiapoptosis status. Adding L. plantarum JM113 significantly raised (P < 0.05) propionic acid, n-butyric acid, and total short-chain fatty acids concentrations in cecal contents of birds fed with DON diet. In addition, DON exposure altered bacterial community structure and disturbed the abundance of several bacterial phyla, families, and genera, leading to dysbiosis. Supplementation with JM113 shifted the gut microbiota composition to that of the CON group. Finally, Spearman correlation analysis suggested that most positive correlations with the mRNA expression of immunity-related and apoptosis-regulatory gene were observed within the phylum Bacteroidetes, and most negative correlations with the indicators were observed within the phylum Firmicutes. The mRNA expression of Bcl-2, TLR2, mTOR, Raptor, and RPS6KB1 (P < 0.05), which are regarded as important cell proliferation and antiapoptosis parameters, were significantly negatively associated with the relative abundances of norank_f__Erysipelotrichaceae, Subdoligranulum, and Anaeroplasma, whereas they had a strong positive correlation with Ruminococcaceae_UCG-004, Alistipes, and Ruminococcaceae_NK4A214_group. These results implied that L. plantarum JM113 supplementation could ameliorate DON-induced apoptosis and intestinal inflammation via manipulating the bacterial community composition and could be used as a potential candidate to attenuate intestinal impairments.